SINEGRITAS AKADEMIKA DAN MASYARAKAT DALAM MEMBANGUN DESA BERSAMA MAHASISWA KKN REGULER UCY DI PADUKUHAN SINDET - Putri, Prihastini Oktasari; Firdaus, Mustakim; Fauziah, Resvi Septiani; Khasanan, Siti Nur (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
The Regular Community Service Program (KKN) of UCY XLIII 2024 Group 1 with the theme "Academic and Community Synergy in Village Development" is a manifestation of community service in integrating campus learning with community life. As an educational institution with awareness of its important role in national progress, UCY participates in village development efforts through the KKN Program. In its implementation, there are two types of activities: main activities and supporting activities. In the main KKN activities, students actively collaborate with the community in conducting education, socialization, and innovation activities as strategic steps in advancing the village. Additionally, students also play a role in efforts to improve economic, food, social, educational, and cultural resilience of the community, as well as creatively and independently optimizing human and natural resources. Furthermore, students are also expected to develop interpersonal skills to build partnerships, interdisciplinary team cooperation, and leadership in managing village potentials. Meanwhile, for supporting activities, students are asked to apply their knowledge according to their respective fields of study.